2014
DOI: 10.2174/1874841401407010001
|View full text |Cite
|
Sign up to set email alerts
|

Beneficiation of Oil Shale by Froth Flotation: Critical Review

Abstract: Oil shale beneficiation by froth flotation hasn't received enough attention in the last two decades. The reason was the economics of the process as well as its environmental impact. However, the recent surge in oil price and recent developments in fine grinding technologies may improve the efficiency of oil shale beneficiation by such process. In this work, oil shale concentration by froth flotation technique was critically reviewed. It was found that most of the work was conducted by conventional mechanical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Oil shale is a sedimentary rock that contains insoluble kerogen as a combustible organic component. It is considered as the second largest fossil fuel deposit worldwide (Tissot and Welte, 1984;Hruljova et al, 2013;Al-Thyabat et al, 2014). Recently oil shale is assumed to serve as alternative energy due to great lack of energy (Larsen et al, 2000;Savest et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Oil shale is a sedimentary rock that contains insoluble kerogen as a combustible organic component. It is considered as the second largest fossil fuel deposit worldwide (Tissot and Welte, 1984;Hruljova et al, 2013;Al-Thyabat et al, 2014). Recently oil shale is assumed to serve as alternative energy due to great lack of energy (Larsen et al, 2000;Savest et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, until now, only a few articles have concentrated on oil-shale flotation. Thyabat et al (2014) thought that flotation could improve the grade of low-grade oil shale. Altun et al (2009) used ultrasonically aided flotation to improve the floatability of oil shale and concluded that the particulates filling the pores/voids or attached to the surfaces of the larger particles were effectively removed after ultrasonic treatment.…”
Section: Introductionmentioning
confidence: 99%